Tantangan Transformasi Model Bisnis Digital UMKM dalam Ekosistem Tiktok Shop: Analisis Fiqh Muamalah Terhadap Akad Digital dan Digital Gharar (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The development of social commerce has transformed the business model of micro, small, and medium enterprises (MSMEs) through the use of digital platforms such as TikTok Shop, which integrate social media, live streaming, and transaction systems into one ecosystem. This study aims to analyze the transformation of MSMEs' digital business models within the TikTok Shop ecosystem and assess their compliance with the principles of Islamic jurisprudence (fiqh muamalah). The study employed a qualitative approach with case study and library research methods. Data were collected through digital observation, document analysis, and literature review covering scientific journals, regulations, and contemporary Islamic jurisprudence (fiqh muamalah) books. Data were then analyzed descriptively and interpretively using the Technology Acceptance Model (TAM), social commerce theory, and Islamic jurisprudence (qawā‘id). The results show that TikTok Shop increases MSMEs' visibility, interaction, and sales through its live commerce feature and algorithm-based marketing. From a fiqh muamalah perspective, digital transactions on this platform are permissible as long as they meet the principles of clarity of the contract (bayyinah), the willingness of the parties (tarāḍī), and are free from gharar and tadlīs. The research also identified potential violations of Sharia business ethics in the form of product visual manipulation, excessive promotion, and unclear product information. These findings emphasize that the success of MSME digital transformation must be balanced with the application of Islamic business ethics principles to ensure fair, transparent, and sustainable digital transactions.